Novel mutation in the choroideremia gene and multi-Mendelian phenotypes in Spanish families. Issue 10 (24th January 2018) - de Castro-Miró, Marta; Tonda, Raul; Marfany, Gemma; Casaroli-Marano, Ricardo P; Gonzàlez-Duarte, Roser
Abstract : Aims: We aimed to accurately diagnose several retinitis pigmentosa (RP) patients with complex ocular phenotypes by combining massive sequencing genetic diagnosis and powerful clinical imaging techniques. Methods: Whole-exome sequencing (WES) of selected patients from two RP families was undertaken. The variants identified were validated by Sanger sequencing and cosegregation analysis. Accurate clinical re-evaluation was performed using electrophysiological and visual field records as well as non-invasive imaging techniques, such as swept-source optical coherence tomography and fundus autofluorescence. Results: The WES results highlighted one novel and one reported causative mutations in the X-linked choroideremia gene ( CHM ), which challenged the initial RP diagnosis. Subsequent clinical re-evaluation confirmed the choroideremia diagnosis. Carrier females showed different degrees of affectation, even between twin sisters, probably due to lyonization. A severe multi-Mendelian phenotype was associated with coincidental dominant pathogenic mutations in two additional genes: PAX6 and PDE6B . Conclusions: Genetic diagnosis via massive sequencing is instrumental in identifying causative mutations in retinal dystrophies and additional genetic variants with an impact on the phenotype. Multi-Mendelian phenotypes previously ascribed to rare syndromes can thus be dissected and molecularly diagnosed. Overall, the combination of powerful genetic diagnosis and clinical non-invasive imaging techniques enables efficient management of patients and their prioritisation for gene-specific therapies.